The Illyrian adventure - Alexander, Lloyd (New York : Bantam Doubleday Dell Books for Young Readers, 1986)
Vesper Holly's going on the adventure of a lifetime! She and her guardian Brinnie are setting sail for the tiny country of Illyra to search for the legendary treasure and army of magical warriors that belonged to old King Vartan.
Keywords: Fiction